Initial freezing point of Mozzarella cheese - Ribero, Gustavo Gabriel (2007)
The initial freezing point in unsalted fresh Mozzarella cheese was measured. The influence of the water-soluble solids on the freezing point depression of unsalted Mozzarella cheese was analyzed. Central temperature profiles and the initial freezing point of unsalted cylindrical cheese samples (1 cm radius; 3 cm height) were determined. A lyophilized aqueous extract of the soluble solids at pH 4.6 was obtained from the unsalted cheese. Initial freezing points of the solutions, prepared with a concentration of soluble solids similar to the one occluded in unsalted cheese matrix and different NaCl concentrations, were determined. Initial freezing points of the unsalted cheese were in the range of -1.2 to -2.4 ºC, while a value of -1.7 ± 0.1 0C was observed in the solution of soluble solids without NaCl. Moreover, the initial freezing points of the solutions of soluble solids and NaCl showed an additional depression of approximately -1.7 0C compared to the initial freezing point of NaCl solutions. Therefore, it was clearly shown that not only NaCl but also the other soluble solids present in the aqueous phase significantly contribute to the freezing point depression of Mozzarella cheese.